Effects of bleomycin A5 on cell cycle of Chinese hamster ovary cells - XUE Shao-bai; CHENG Zhi-hua; LIU Hui-tu; LI Shu-wen; ZHANG Hong-qing; CHENG Ru-xuan; HU Yun-ying; XU Pu (Acta Pharmacologica Sinica; Vol 5, No 2 (June 1984): Acta Pharmacologica Sinica, 2016)
The effect of bleomycin A5 on the cell cycle of Chinese hamster obvary cells was studied by microflurophotometry, flow cytometry and cell cycle analyses. The progress of G1→S→G2 was not affected by bleomycin A5 but the cells were blocked on the G2 phase.